Utilization of sexual and reproductive health services among young people in refugee settings in Uganda - Bukuluki, Paul Mukisa Wako; Kisaakye, Peter; Wandiembe, Symon Peter; Kiwujja, Victor; Kajungu, Christine; Mugwanya, Wilberforce; Nabakooza, Shakira; Anyii, Cyprian; Kaikai, Fiona (Frontiers in Reproductive Health, 2023)
There is a considerable high level of unmet need for reproductive health services among refugees. Yet, there is limited research about the provision and utilization of sexual and reproductive health (SRH) services among young people in refugee settings. Drawing on a sample of 575 young refugees (15–24 years) from a cross-sectional survey, this study aims to fill this gap by identifying the factors associated with SRH utilization among young people living in refugee settings in Northern Uganda. The utilization of SRH services at the health facilities was significantly different between female and male young people after adjusting for all other variables (aOR = 2.46, 95% CI, 1.58, 3.84). Young people who were not living in a marital union (aOR = 0.38, 95% CI, 0.20, 0.71), or held inequitable gender norms about services (aOR = 0.28, 95% CI, 0.12, 0.66) had about a third of the odds of utilizing SRH services. Young women with comprehensive knowledge about contraception, modern contraceptives, and HIV and STI prevention, had more than twice the odds of utilizing SRH services (aOR = 2.23, 95% CI, 2.67, 6.90). There is need to integrate social norm measurements and social norm change strategies in strategies for promoting utilization of SRH services among refugees in low-income countries especially in Uganda